Territorial dimension of wheat production in Romania - Marian Zaharia; Rodica-Manuela Gogonea; Aniela Bălăcescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Romania's significant agricultural productive potential can fully cover domestic demand and can ensure important export deliveries. However, the yield of cereal production is below the European Union average. Of these, an important place is occupied by wheat production. Taking into account these aspects, the paper investigates the potential of wheat production in Romanian counties starting from a set of indicators and using cluster analysis to identify similarities and disparities between counties from this point of view. Through this study we tried to provide answers to the questions: What is the configuration of wheat production yield at the regional level in Romania? What is its evolution over time? The results obtained during the research show that there are disparities in the counties of Romania in terms of the efficiency of wheat production in correlation with the resources used for its production.
Keywords: C10; C38; O13; 330; agricultural sector; wheat production; production yield; regional development; Romania